ІННОВАЦІЙНІ ЦИФРОВІ ТЕХНОЛОГІЇ ЯК ДРАЙВЕР ТРАНСФОРМАЦІЇ СИСТЕМИ СУЧАСНОГО СПОРТИВНОГО МЕНЕДЖМЕНТУ - СИВОХОП, ЕДУАРД; СЕМАЛЬ, НАТАЛІЯ; БІЛОГУР, ВЛАДА (Humanities Studies, 2025)
The article examines the role of innovative digital technologies as a key driver of the transformation of modern sports management. The aim of the article is a comprehensive analysis of the impact of innovative digital technologies on the transformation of the modern sports management system and the determination of their potential for increasing the efficiency of sports organization management, athlete training and interaction with the audience. The objectives of the study: 1) to investigate modern innovative digital technologies in sports management, digital platforms for managing sports organizations; 2) to identify the impact of digital technologies on the efficiency of sports management, including the optimization of management processes, increasing the performance of athletes; 3) to analyze foreign experience in implementing digital innovations in sports in order to identify practices that can be adapted in Ukraine; 4) to identify prospects and recommendations for integrating digital technologies into the modern sports management system. The main trends in the digitalization of sports organizations are considered, including the use of big data analytics, athlete performance management systems, communication and marketing platforms, as well as tools for increasing the commercial attractiveness of teams and events. The positive impact of digital solutions on the optimization of management processes, increasing the performance of athletes and the competitiveness of sports organizations is highlighted. The prospects for the introduction of the latest technologies into sports management and recommendations for increasing the efficiency of their integration are presented. The article will be useful for sports management specialists, digital technology analysts and researchers in the field of innovative sports development. It is concluded that the integration of digital technologies into the sports management system creates conditions for increasing the competitiveness of sports organizations, effective resource management and the development of innovative models of interaction with athletes, coaches and fans. The prospects of digitalization indicate that modern sports management in the coming years will transform into an integrated system capable of quickly adapting to technological changes and ensuring sustainable development of the industry.